2010
DOI: 10.1264/jsme2.me10102
|View full text |Cite
|
Sign up to set email alerts
|

TonB-Dependent Receptors in Nitrogen-Fixing Nodulating Bacteria

Abstract: TonB-dependent receptors (TBDRs) allow Gram-negative bacteria to uptake scarce resources from competitive environments with very high affinity. Early reports on TBDRs focused on the uptake of siderophore-iron complexes but recent studies have showed that the spectrum of ligands includes sugars, vitamins, heme, and other non-ferrous cations. To investigate the possible roles of TBDRs in nitrogen-fixing, nodulating bacteria, a bioinformatics approach was adopted to identify their presence in the genome of 13 sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Under low-iron conditions, the growth of the ⌬irrB strain was significantly reduced and the bhuA gene was downregulated, findings similar to those for A. tumefaciens and Brucella abortus (26,27). In MSR-1, bhuA is annotated as a putative TonB-dependent receptor that is located in the outer membranes and facilitates the acquisition of scarce resources in an energy-dependent manner (28). These findings suggest that IrrB is required for the induction of bhuA transcription in response to low-iron conditions and that irrB deletion disrupts iron uptake.…”
Section: Discussionsupporting
confidence: 60%
“…Under low-iron conditions, the growth of the ⌬irrB strain was significantly reduced and the bhuA gene was downregulated, findings similar to those for A. tumefaciens and Brucella abortus (26,27). In MSR-1, bhuA is annotated as a putative TonB-dependent receptor that is located in the outer membranes and facilitates the acquisition of scarce resources in an energy-dependent manner (28). These findings suggest that IrrB is required for the induction of bhuA transcription in response to low-iron conditions and that irrB deletion disrupts iron uptake.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to having variations in symbiosis (24, 39, 60), various members of the Bradyrhizobiaceae , including Bradyrhizobium , harbor diverse biochemical functions such as photosynthesis, nitrification, sulfur oxidation, aromatic degradation, and oligotrophy (22, 25, 26, 33, 34, 45, 56, 68, 70). Thus, a long-standing question is how the members of the Bradyrhizobiaceae have acquired these diverse biochemical features.…”
mentioning
confidence: 99%
“…Analysis of the genome of 13 selected Rhizobiaceae strains revealed that the number of TBDT-like genes ranged from one in Mesorhizobium loti MAFF303099 to 14 in Azorhizobium caulinodans ORS571 (Lim 2010). The majority of the 54 rhizobial TBDTs identifi ed in that study are predicted to be involved in the uptake of iron-siderophore (26) or heme (13).…”
Section: Transporters For Metal Uptake Through the Outer Membranementioning
confidence: 95%